Neonatal Sepsis and its Associated Risk Factors in Albatool Teaching hospital / Diyala / Iraq - Mohammed Jameel , Douaa; Jasim Mohammed, Aseel; Qais Almaaroff, Sura; Mansour Hamza , Shefaa (Diyala Journal of Medicine, 2020)
Background: Fifty percent of newborns may die because of neonatal sepsis who are not treated. The incidence augmented during the recent years. It may be due to the more public use of aggressiveprocesses and the growth of tough organisms. Objective: To recognize factors (Ante – perinatal) that lead to sepsis (early or late) in newborn period in Albatool teaching hospital/Diyala/Iraq. Patients and Methods: A case-control study done in the Department of Pediatrics in Al-Batool Teaching Hospital, Diyala, Iraq during a period of seven months from Sept 2017 to April 2018. It comprised 200 neonates aged ≤ 28 days. One-handered of them were presented to the hospital because of neonatal sepsis (case group) and the other 100 included neonates presented to the hospital because of other reasons (control group). A questionnaires were used to collect the essential information including demographic and clinical data for the neonates and their mothers. Results: The mean age of neonates was 8.59 ± 7.28 days. Four factors were found to be noteworthy independent risk factors for neonatal sepsis. These factors were pre mature rupture membrane,presence or obscene odor discharge, intrapartum fever, and the prerequisite for resuscitation. Conclusion: Both maternal and neonatal factors had contributed to the risk of neonatal sepsis. The onset of neonatal sepsis was higher in the first week of life.